Intercropping With Turmeric or Ginger Reduce the Continuous Cropping Obstacles That Affect Pogostemon cablin (Patchouli) - Zeng, Jianrong; Liu, Jianzhong; Lu, Changhua; Ou, Xiaohua; Luo, Keke; Li, Chengmei; He, Mengling; Zhang, Hongyi; Yan, Hanjing (Frontiers in Microbiology, 2020)
Continuous cropping can restrict the development of the medicinal plant cultivation industry because it alters soil properties and the soil microbial micro-ecological environment. It can also lead to reductions in the chemical contents of medicinal plants. In this study, we intercropped continuously cropped Pogostemon cablin (patchouli) with turmeric or ginger. High-throughput sequencing was used to study the soil bacteria and fungi. Community composition, diversity, colony structure, and colony differences were also analyzed. A redundancy analysis (RDA) was used to study the interactions between soil physical and chemical factors, and the bacteria and fungi. The correlations between the soil community and the soil physical and chemical properties were also investigated. The results showed that intercropping turmeric and ginger with patchouli can improve soil microbial abundance, diversity, and community structure by boosting the number of dominant bacteria, and by improving soil bacterial metabolism and the activities of soil enzymes. They also modify the soil physical and chemical properties through changes in enzyme activity, soil pH, and soil exchangeable Ca (Ca). In summary, turmeric and ginger affect the distribution of dominant bacteria, and increase the contents of the active ingredient in patchouli. The results from this study suggested that the problems associated with the continuous cropping of patchouli can be ameliorated by intercropping it with turmeric and ginger.